Mechanical Properties of Inconel Alloy 718 Produced by 3D Printing using DMLS - Dana, Milan; Zetkova, Ivana; Mach, Josef (Manufacturing Technology Journal, 2018)
Additive manufacturing (AM) allows printing from different materials: from wax to plastic and even metal. This paper concentrates on Direct Metal Laser Sintering (DMLS), which allows printing to create complex parts from different kinds of metal. Inconel 718 was chosen for this research. This material is used especially in the aerospace industry and in other demanding applications due to its characteristic properties, which include high strength at high temperatures, corrosion resistance, low thermal conductivity, high hardness, work hardening and low thermal conductivity. Components used in aeroplanes must be very reliable, lightweight and their mechanical stresses must be accurately described, because the components are designed with respect to these criteria. For this reason, each material must be perfectly described in terms of mechanical properties and their minimum limits must be identified. Tensile testing is the best way to find the basic set of mechanical properties of a material. The samples were printed in two different orientations on a building platform and the differences in mechanical properties were investigated. The effect of machining on mechanical properties was also investigated.
Keywords: 3D print; DMLS; Inconel 718; Tensile strength